Identidad personal y nacional - Carrera Ticliahuanca, Leidy Angela (2019)
The session titled the personal and national Identity, in Secondary Education students, was executed in the area of Personal Development, citizenship and civic with students of the fifth grade of Secondary Education of the Educational Institution Kepler I.E.P ._x000D_ The purpose of the session is to reflect on the importance of personal and national identity to face the problems of life, it was carried out through the use of the reflexive method and its different studies.